2012
DOI: 10.1007/s10750-012-1301-z
|View full text |Cite
|
Sign up to set email alerts
|

Species distribution and assembly patterns of frog larvae in rainforest streams of Madagascar

Abstract: Many tropical rainforests harbour speciesrich assemblages of frogs and, consequently, of tadpoles. These larvae are often morphologically highly diverse, especially in their oral structures. Whether this might represent an important axis of ecological partitioning in frog assemblages remains an untested hypothesis. In general, it is poorly known how diverse tadpole assemblages are organised. Using information from Madagascar's remarkably species-rich stream tadpole assemblages, we analysed the distribution and… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
14
0
5

Year Published

2014
2014
2021
2021

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 19 publications
(19 citation statements)
references
References 44 publications
0
14
0
5
Order By: Relevance
“…For larvae, a dataset of 117 characters for 170 mantellid species was assembled for this study, based on tadpole voucher specimens that had previously been identified by DNA barcoding25. Data sets of adult and tadpole measurements overlapped and were jointly analysed for 113 mantellid species.…”
Section: Methodsmentioning
confidence: 99%
“…For larvae, a dataset of 117 characters for 170 mantellid species was assembled for this study, based on tadpole voucher specimens that had previously been identified by DNA barcoding25. Data sets of adult and tadpole measurements overlapped and were jointly analysed for 113 mantellid species.…”
Section: Methodsmentioning
confidence: 99%
“…We also recognised seven types of mouthparts, according to the classification proposed by Strauß et al. (): sand eater, reduced teeth, generalised, podgy generalised, fossorial, suctorial and funnel mouthed. Among these, generalised and funnel‐mouthed groups account for more than 70% and 10% in abundance, respectively, of all tadpoles.…”
Section: Methodsmentioning
confidence: 99%
“…We recorded 27 tadpole species (Ramamonjisoa, 2017) belonging to four genera of Mantellidae: Mantidactylus, Boophis, Spinomantis, Gephyromantis and Guibemantis. We also recognised seven types of mouthparts, according to the classification proposed by Strauß et al (2013): sand eater, reduced teeth, generalised, podgy generalised, fossorial, suctorial and funnel mouthed. Among these, generalised and funnel-mouthed groups account for more than 70% and 10% in abundance, respectively, of all tadpoles.…”
Section: Me Th Odsmentioning
confidence: 99%
See 1 more Smart Citation
“…Umbelliform oral apparatus or funnel-mouths, are generally hypothesized to be used in microphagous filter-feeding from the surface tension (e.g. Smith 1926;Inger et al 1986;Hoff et al 1999;Altig et al 2007;Grosjean et al 2011;Strauß et al 2013). However, there is evidence that this might not hold true, at least in some tadpole species.…”
Section: Table 2 (Continued)mentioning
confidence: 99%